Protective effect of mulberry flavonoids on sciatic nerve in alloxan-induced diabetic rats - Ma Song-Tao; Liu Dong-lian; Deng Jing-jing; Peng Yan-juan (Universidade de São Paulo, 2014)
Mulberry leaves (Morus alba L.) are a traditional Chinese medicine for blood serum glucose reduction. This study evaluated the protective effects of mulberry flavonoids on sciatic nerve in alloxan-induced diabetic rats. In this study, 80 Sprague-Dawley rats were divided into five groups: A (control), B (diabetic treated with saline), C-D (diabetic treated with 0.3, 0.1 g/kg mulberry flavonoids once a day for 8 weeks) and E (diabetic treated with 0.3 mg/kg methycobal). The diabetic condition was induced by intraperitoneal injection of 200 mg/kg alloxan dissolved in saline. At the end of the experimental period, blood, and tissue samples were obtained for biochemical and histopathological investigation. Treatment with 0.3 g/kg mulberry flavonoids significantly inhibited the elevated serum glucose (P< 0.01). The increased myelin sheath area (P< 0.01), myelinated fiber cross-sectional area and extramedullary fiber number (P< 0.05) were also reduced in alloxan-induced rats treated with 0.3 g/kg mulberry flavonoids. 0.3 g/kg mulberry flavonoids also markedly decreased onion-bulb type myelin destruction and degenerative changes of mitochondria and Schwann cells. These findings demonstrate that mulberry flavonoids may improve the recovery of a severe peripheral nerve injury in alloxan-induced diabetic rats and is likely to be useful as a potential treatment on peripheral neuropathy (PN) in diabetic rats.